Efficient Phytase Secretion and Phytate Degradation by Recombinant Bifidobacterium longum JCM 1217 - Sun, Zhongke; Yue, Zonghao; Yang, Xingdong; Hao, Xinqi; Song, Maoping; Li, Lili; Chen, Can; Chu, Cuiwei; Li, Chengwei (Frontiers in Microbiology, 2019)
Genetic engineering of probiotics, like bifidobacteria, may improve their microbial cell factory economy. This work designed a novel shuttle plasmid pBPES, which bears exogenous appA and is stable within Bifidobacterium longum JCM 1217. Cloning of three predicted promoters into pBPES proved that all of them drive appA expression in B. longum JCM 1217. Transformation of plasmids pBPES-tu and pBPES-groEL into B. longum JCM1217 resulted in much more phytase secretion suggests Ptu and PgroEL are strong promoters. Further in vitro and in vivo experiments suggested B. longum JCM 1217/pBPES-tu degrades phytate efficiently. In conclusion, the study screened two stronger promoters and constructed a recombinant live probiotic strain for effectively phytase secretion and phytate degradation in gut. The strategy used in the study provided a novel technique for improving the bioaccessibility of phytate and decreasing phosphorus excretion.